The Prototype of the Neo- heat exchanger from exchaust gas motor diesel - Hatta Dahlan; Ahmad Darwis (Universitas Sriwijaya, 2016)
The use of diesel motor Â may be to increase Â with the development of the medium industry in the last time. The energy crisis that befell the world industry still felt until this time while increasing energy consumption resulting in the ability of the electric power supplied by PLN still limited which culminated with the drop current (byar-pet) electricity.More information from this development diesel motor sales continues to increase and growing fast. Along with the luster of diesel engine appears in the new issue is the increasing air pollution coming out of diesel engines that have a negative impact on the surrounding environment.Heat exhaust gas from diesel motor still not useable diesel as an alternative energy source for heat boiler and other uses.This research done for exploiting the exhaust from diesel engines with prototyping appliance heat exchanger(heat exchanger) shaped double tubes 1 pass shell 2 pass tubes. The Neo-heat exchanger consists of a tube with a diameter of the jug 0.426 ft, long 1.48 ft. The diameter of the tube 0,032 ft, the length of the 1,148 ft .The total length of the tube 22,956 ft. The measurement was conducted with record gas temperature and heat out from diesel.,The results of this study found that the hot gas that comes out of the motor fuel is 183,608 F, hot gas that comes out of the prototype HE was 145,382F with energy fraction of heat 27.44 percent and heat efficiency of 67.5% in accordance with standard conditions.